Identification and Characterization of TMEM119-Positive Cells in the Postnatal and Adult Murine Cochlea - Mohamed Bassiouni; Alina Smorodchenko; Heidi Olze; Agnieszka J. Szczepek (Brain Sciences, 2023)
Transmembrane protein 119 (TMEM119) is expressed in a subset of resident macrophage cells of the brain and was proposed as a marker for native brain microglia. The presence of cells expressing TMEM119 in the cochlea has not yet been described. Thus, the present study aimed to characterize the TMEM119-expressing cells of the postnatal and adult cochlea, the latter also after noise exposure. Immunofluorescent staining of cochlear cryosections detected TMEM119 protein in the spiral limbus fibrocytes and the developing stria vascularis at postnatal Day 3. Applying the macrophage marker Iba1 revealed that TMEM119 is not a marker of cochlear macrophages or a subset of them. In the adult murine cochlea, TMEM119 expression was detected in the basal cells of the stria vascularis and the dark mesenchymal cells of the supralimbal zone. Exposure to noise trauma was not associated with a qualitative change in the types or distributions of the TMEM119-expressing cells of the adult cochlea. Western blot analysis indicated a similar TMEM119 protein expression level in the postnatal cochlea and brain tissues. The findings do not support using TMEM119 as a specific microglial or macrophage marker in the cochlea. The precise role of TMEM119 in the cochlea remains to be investigated through functional experiments. TMEM119 expression in the basal cells of the stria vascularis implies a possible role in the gap junction system of the blood–labyrinth barrier and merits further research.